Governing Global Production - Wilson, J. author. aut Link
X, 227 p.
Keywords: Northeast Asian steel industries have developed global production networks, but by spanning multiple national spaces, these networks unite many national economies while belonging exclusively to none. Who, therefore, is in control? Jeffrey D. Wilson examines how states and firms coordinate their activities to govern global production.